Introductory Particle Physics - Gates, Frederick (New York : NY Research Press, 2019)
Particle physics studies the fundamental constituents of matter and radiation and their interactions. Fundamental particles exhibit wave-particle duality and are represented using quantum state vectors in Hilbert space. All elementary particles and their interactions are understood using a quantum field theory, which is called the Standard Model. This model accounts for 61 particles, among which are 24 fermions, 8 gluons, the photon and W-, W+ and Z bosons. The Standard Model further describes the fundamental interactions of these particles, such as electromagnetic, strong and weak interactions. Particle physics has enriched human lives with the production of medical isotopes for use in external beam radiotherapy and PET imaging, development of touchscreen technology and the World Wide Web. This book is a valuable compilation of topics, ranging from the basic to the most complex theories and principles in the field of particle physics. The topics included herein are of utmost significance and bound to provide incredible insights to readers. This textbook is appropriate for particle physicists, high-energy physicists, phenomenologists, field theorists, students and other experts associated with this field.
Keywords: Particle physics